Pendidikan Keluarga Seimbang yang Melekat Sebagai Basis yang Mencerahkan Anak di Era Digital - Rahmatullah, Azam Syukur (IAIN Ponorogo, 2017)
The degree of behavioral deviation done by children in the present era is increasingly apprehensive, especially in the digital era which anything seems sophisticated resulting children are